2021
DOI: 10.1111/bph.15646
|View full text |Cite
|
Sign up to set email alerts
|

A role for translational regulation by S6 kinase and a downstream target in inflammatory pain

Abstract: Background and Purpose Translational controls pervade neurobiology. Nociceptors play an integral role in the detection and propagation of pain signals. Nociceptors can undergo persistent changes in their intrinsic excitability. Pharmacological disruption of nascent protein synthesis diminishes acute and chronic forms of pain‐associated behaviours. However, the targets of translational controls that facilitate plasticity in nociceptors are unclear. Experimental Approach We used ribosome profiling to probe the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…A third report found that deletion of TRPC5 increased mechanical sensitivity following partial meniscectomy and intraarticular injection of monoiodoacetate (MIA)—the latter of which was used to induce a model of osteoarthritis (de Sousa Valente et al, 2020). The increased sensitivity following MIA injection was also correlated with increased c‐Fos expression in cultured neurons, which is significant given that c‐Fos has been implicated as playing a key role in the transition to chronic forms of inflammatory and neuropathic pain via the downstream expression of dynorphin (Ahmad & Ismail, 2002; Marvaldi et al, 2020; de la Peña, Kunder, et al, 2021).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…A third report found that deletion of TRPC5 increased mechanical sensitivity following partial meniscectomy and intraarticular injection of monoiodoacetate (MIA)—the latter of which was used to induce a model of osteoarthritis (de Sousa Valente et al, 2020). The increased sensitivity following MIA injection was also correlated with increased c‐Fos expression in cultured neurons, which is significant given that c‐Fos has been implicated as playing a key role in the transition to chronic forms of inflammatory and neuropathic pain via the downstream expression of dynorphin (Ahmad & Ismail, 2002; Marvaldi et al, 2020; de la Peña, Kunder, et al, 2021).…”
Section: Resultsmentioning
confidence: 88%
“…Taken together, these results point to future avenues of osteoarthritic pharmaceutical development that could jointly address pain management and joint morphology through combined targeting of NGF, MMP13, and IL‐1B. In addition to these genetic models, local injection of NGF has been used as a key inflammatory mediator in behavioral models given that NGF serves as a potentiator of protein synthesis (Barragan‐Iglesias et al, 2021; Melemedjian et al, 2010; de la Peña, Barragan‐Iglesias, et al, 2021; de la Peña, Kunder, et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the initiation phase of protein synthesis has garnered substantial attention, relatively little is known regarding elongation. Inhibitors that prevent translation elongation diminish pain amplification behaviors 26,29,98 . Given that inflammatory mediators increase ribosome occupancy in 5′UTRs, it would be interesting to determine what effects eIF5A inhibition has on translation start sites and if they mirror those increased by inflammatory cues 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of inflammatory mediators on translation have recently been reported using ribosome profiling 28 . Within 20 min, translation of immediate early genes such as Arc and c‐Fos is increased as is the utilization of cryptic open reading frames situated in the 5′ untranslated region of numerous transcripts including calca/CGRP 28–30 . Despite the pervasive roles of translational regulation in preclinical murine models, it remains somewhat tenuous if translational regulation is a broadly conserved pathway for nociceptor sensitization.…”
Section: Introductionmentioning
confidence: 99%